Water injection to maintain energy of oil reservoir in fractured basement rocks - Quang Ngoc Pham (Petrovietnam Journal, 2015)
After the 40s of the 20th century, water injection technology for reservoir pressure maintenance has been applied in many oil fields and significantly increased oil recovery factor [10]. Today, it is considered a popularly applied method in most producing oil fields in the world. In this paper, the author presents some issues relating to water injection for fractured basement reservoirs such as investigation of the injected water movement, water coning mechanism, timing justification for water injection, optimisation of injection water volume, and injection well locations.